Heavy Metal Concentration in Fruit Samples During the Dry Season From three Major Markets in Enugu, Nigeria - Ameh, G.I.; Ogbodo, L.C.; Nwani, C.D (Canadian Journal of Agriculture and Crops, 2020)
The dynamics of seasonal changes of heavy metals composition in three common edible fruits in Enugu State, Nigeria were analyzed. Banana, pineapple and watermelon samples were collected during the three dry season months (December, January and February) from the three markets in the three senatorial districts of the state (Nsukka market, Ezeagu market, and Ogbete market). Heavy metals evaluated during the study include lead, cadmium, cobalt, nickel, zinc and copper. Samples digestion was done using wet digestion method which comprises a mixture of acids and hydrogen peroxide. Metals in the samples were quantified using atomic absorption spectrophotometry (AAS) at specific wave lengths and values reported in mg/kg. Among the three samples for all metals studied, maximum and minimum values are; 0.28 – 0.03 mg/kg, 0.22 – 0.01 mg/kg, 0.13 – 0.01 mg/kg, 0.64 – 0.33 mg/kg, 0.69 – 0.01 mg/kg and 13.88 – 1.42 mg/kg for lead, cadmium, nickel, cobalt, copper and zinc respectively. The quantities of metals in all the samples in average increased with progression in dry season. The heavy metals analyzed were more in banana and least in watermelon samples. Values obtained were compared to WHO maximum permissible limit for each metal.